2015
DOI: 10.21608/eos.2015.78729
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of labial corticotomy vs palatal corticotomy during en masse retraction with mini screws as anchorage units

Abstract: Aim:Aim: Aim: Aim: The aim of this study was to evaluate and compare the treatment effects and duration of en-masse retraction combined with labial corticotomy and that with palatal corticotomy using miniscrews as source of anchorage. Methods:Methods: Methods: Methods: Twenty adult patients with bimaxillary or maxillary protrusion requiring orthodontic treatment with upper anterior retraction in the extraction space of first premolars were selected. Patients were divided into two groups; labial corticotomy gru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…For group I, the results of the current study showed that the time needed for extraction space closure was in agreement with El Gemeay et al, (12) and Wilcko et al, (24) for the upper arch. The results of the lower arch in this study matched those of Lino et al, (6) who declared that en-masse retraction of the lower arch could be achieved in 7 months while Khatri el al., (11) reported space closure time of 6 months after corticotomy which could be attributed to the difference in anchorage preservation method.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…For group I, the results of the current study showed that the time needed for extraction space closure was in agreement with El Gemeay et al, (12) and Wilcko et al, (24) for the upper arch. The results of the lower arch in this study matched those of Lino et al, (6) who declared that en-masse retraction of the lower arch could be achieved in 7 months while Khatri el al., (11) reported space closure time of 6 months after corticotomy which could be attributed to the difference in anchorage preservation method.…”
Section: Discussionsupporting
confidence: 91%
“…Corticotomy assisted en-masse retraction was evaluated in previous studies. (9)(10)(11)(12) It was found that the rate of retraction was accelerated in the first two months after corticotomy. (9,11) A significant reduction in retraction time after first premolar extraction was reported when a corticotomy group was compared to a control one.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation